FACTORS AFFECTING CRIME RATE IN BANDAR LAMPUNG - Erika Armadona; Zainudin hasan; Ratu Saka Ganta (Sahabat Publikasi, 2023)
The increasing prevalence of news about crime that occurs, both through electronic media and other media to perceptions from the public seems to never run out to be discussed. In the calculation of the Central Statistics Agency, in 1 minute 32 seconds there was 1 criminal act in Indonesia. Meanwhile, out of 100,000 people in Indonesia, 140 of them are at risk of crime. The high crime rate is influenced by several factors such as education, less strict laws, high unemployment and inadequate wages. The purpose of this study is to determine the motives that cause criminal acts in Bandar Lampung and to determine the factors that influence the occurrence of criminal acts in Bandar Lampung. This type of research is a type of qualitative descriptive and quantitative descriptive research with the nature of research, namely explanatory. The data used in this study is skunder data in the form of time series data from the Central Statistics Agency and other related institutions. While other data sources are primary data, namely observations made by researchers and interviews with several related parties. The analysis method used for secondary data is Ordinary Least Square (OLS) using multiple linear regression. The results of this study that partially each variable does not have an influence on crime that occurs in Bandar Lampung. But simultaneously together education, unemployment, GRDP and per capita income affect the occurrence of crime in Lampung. The result of Koefisen determination in this study was 74.7%.